Erythema nodosum after azacitidine in a patient with acute myeloid leukemia - Elham Nasrollahi; Alessio Giubellino; Armin Rashidi (SAGE Journals, 2022)
Introduction
Nodular skin lesions in patients with acute myeloid leukemia (AML) raise clinical suspicion for leukemia cutis versus fungal infections. Here, we report a rare case of treatment-related erythema nodosum (EN) in a patient with AML.
Case Report
Approximately 5 weeks after the initiation of sorafenib and one week after azacitidine initiation, a 32-year-old man with primary refractory AML presented with several painful red nodules on the lower extremities. Histological examination established a diagnosis of EN.
Management and Outcome
Treatment with topical and oral steroids led to complete resolution of the nodules. However, once the dose of steroids was reduced, the lesions rapidly recurred. Higher dose steroids were reinitiated, again with a resolution of the nodules, confirming steroid responsiveness of the underlying process.
Discussion
Given the onset of lesions one week after the initiation of azacitidine and 5 weeks after the initiation of sorafenib, azacitidine was considered the more likely culprit. Only 2 cases of EN-like eruption after azacitidine and 1 case after sorafenib have been reported. Although fungal infections and leukemia cutis are the top differentials considered for skin nodules in a patient with AML, EN should be considered as an alternative diagnosis. Correct diagnosis is critical because it will guide treatment.
Keywords: 111299 Oncology and Carcinogenesis not elsewhere classified; 111599 Pharmacology and Pharmaceutical Sciences not elsewhere classified; 111599 Pharmacology and Pharmaceutical Sciences not elsewhere classified